'Nothing Is Less Universal than the Idea of Race': Alfred Métraux, American Social Science and UNESCO's Anti-Racist Campaign in 1950s Paris. Issue 1 (1st December 2021) - Conklin, Alice L.
Abstract: In 1950, the cultural anthropologist Alfred Métraux, a student of Marcel Mauss, was appointed to head a new Race Bureau at UNESCO in Paris whose mission was to combat racism with the tools of social science. Métraux had worked in the Americas since the 1930s, and his appointment allowed French social scientists to join the global struggle to remove prejudice 'from the minds of men'. To what extent did French scholars help shape Métraux's efforts, given that at the time American sociologists and social psychologists dominated the study of race relations? Booklets commissioned by UNESCO and authored by French and American scientists in the early 1950s suggest that linguistic and conceptual barriers made cross-national discussions of race difficult, but not impossible. Thanks in part to Métraux's campaign, the social scientific study of race relations in post-war France began earlier than is typically remembered.